A dose‐response study of a novel method of selective tissue modification of cellular structures in the skin with nanosecond pulsed electric fields. Issue 4 (2nd August 2019) - Kaufman, David; Martinez, Michelle; Jauregui, Lauren; Ebbers, Edward; Nuccitelli, Richard; Knape, William A.; Uecker, Darrin; Mehregan, Darius
Abstract : Background and Objectives: This study describes the effects of nanosecond pulsed electric fields (nsPEF) on the epidermis and dermis of normal skin scheduled for excision in a subsequent abdominoplasty. NsPEF therapy applies nanosecond pulses of electrical energy to induce regulated cell death (RCD) in cellular structures, with negligible thermal effects. Prior pre‐clinical studies using nsPEF technology have demonstrated the ability to stimulate a lasting immune response in animal tumor models, including melanoma. This first‐in‐human‐use of nsPEF treatment in a controlled study to evaluate the dose‐response effects on normal skin and subcutaneous structures is intended to establish a safe dose range of energies prior to use in clinical applications using nsPEF for non‐thermal tissue modification. Study Design/Materials and Methods: Seven subjects with healthy tissue planned for abdominoplasty excision were enrolled. Five subjects were evaluated in a longitudinal, 60‐day study of effects with doses of six nsPEF energy levels. A total of 30 squares of spot sizes 25mm 2 or less within the planned excision area were treated and then evaluated at 1 day, 5 days, 15 days, 30 days, and 60 days prior to surgery. Photographs were taken over time of each treated area and assessed by three independent and blinded dermatologists for erythema, flaking and crusting using a 5‐point scale (0 = low, 4 = high). Punch biopsies of surgically removed tissue were processed and evaluated for tissue changes using hematoxylin and eosin, trichome, caspase‐3, microphthalmia transcription factor, and elastin stains and evaluated by a dermatopathologist. The skin of two subjects received additional treatments at 2 and 4 hours post‐nsPEF and was evaluated in a similar manner. Results: Most energy settings exhibited delayed epidermal loss followed by re‐epithelization by day 15 and a normal course of healing. Histologic analysis identified the appearance of activated caspase‐3 at two and four hours after nsPEF treatment, but not at later time points. At the 1‐day time point, a nucleolysis effect was observed in epidermal cells, as evidenced by the lack of nuclear staining while the epidermal plasma membranes were still intact. Cellular structures within the treatment zone such as melanocytes, sebaceous glands, and hair follicles were damaged while acellular structures such as elastic fibers and collagen were largely unaffected except for TL6 which showed signs of dermal damage. Melanocytes reappeared at levels comparable with untreated controls within 1 month of nsPEF treatment. Conclusions: The selective effect of nsPEF treatment on cellular structures in the epidermal and dermal layers suggests that this non‐thermal mechanism for targeting cellular structures does not affect the integrity of dermal tissue within a range of energy levels. The specificity of effects and a favorable healing response makes nsPEF ideal for treating cellular targets in the epidermal or dermal layers of the skin, including treatment of benign and malignant lesions. NsPEF skin treatments provide a promising, non‐thermal method for treating skin conditions and removing epidermal lesions. © 2019 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.